Pesan Moral Dalam Buku Kelong-Kelongna Tau Mangkasaraka Karya Kembong Daeng - Bagaskara, Muhammad Arsyil; Agussalim, Andi; H, Hajrah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Kelong is one of the regional literary forms that has been present alongside the activities of the Makassar community since ancient times. The book